The four-category ontology of Edward Jonathan Lowe (review) - Rayhert, Kostiantyn (Actual Problems of Mind, 2018)
The study reviews the Edward Jonathan Lowe’s four-category ontology as a foundation for metaphysics as a theory of categories. The fundamental ontological categories of the E. J. Lowe’s ontology are objects as substantial particulars (i.e. really existed particular singular things), kinds as substantial universals (i.e. class concepts of objects), properties and relations as non-substantial universals (i.e. attributes of classes of objects), and modes as non-substantial particulars (i.e. particular singular attributes of objects). Objects are instantiated by kinds, exemplified by properties and relations, and characterized by modes. Kinds are characterized by properties and relations. Modes are instantiated by properties and relations.